Structural and functional alterations of platelets in pregnant women with preeclampsia - Bakunovich, Andrei V.; Bulanova, Klavdia Ya. (Journal of the Belarusian State University. Ecology, 2019)
The article presents the characteristics of platelets in normal and pathological conditions of pregnancy. The functional state of platelets, especially regulation of their count, reorganization of plasma membrane and intracellular structures, as well as ability of cells to activate in physiological condition and during preeclampsia, are described. The mechanisms of increased platelet aggregation activity in pregnant women with preeclampsia due to changes in the composition of their plasma membranes, intracellular organelles, changes in the content of cytoplasmic calcium, thromboxane A2 and their correlations with other intracellular messengers are considered.